Semantics-cognitive Approach in Russian Linguistics - Sternin, losif A.; Popova, Zinaida D. (Respectus Philologicus, 2006)
The article focuses on on the semantics-cognitive approach in linguistic research, which analyses the relationship between language semantics and the conceptsphere of the nation. The principle position of the given methodology is that it is possible to describe the system of national concepts – the national conceptsphere  while studying the semantics of language signs.
Keywords: concept; conceptosphere; meaning